Multiscale micromechanics modeling of viscoelastic natural plant fibers - Li, Jie; Wang, Jian; Wang, Miao; Tie, Jinxin; Gao, Xuefeng; Wu, Yujie; Song, Jinhua; Xia, Chen (Frontiers in Materials, 2024)
Natural plant fibers are hierarchical structures with microstructural constituents at various scales. With advancements in composite material science, these fibers are widely used in various polymer products. Therefore, it is crucial to quantitatively understand the relationship between their microstructures and mechanical behavior. This paper utilizes the Mori-Tanaka micromechanics model, viscoelasticity theory, and Zakian's inversion method to examine the impact of plant fiber microstructure on the viscoelastic behavior of multiscale structures. At the microscopic scale, macromolecule polymer (matrix) and cellulose (fiber) are homogenized, with a second homogenization involving the cell wall microstructure. The third homogenization considers the cell wall and lumen porosity to predict effective moduli of fiber bundle cells. Using the principle of elastic-viscoelastic correspondence, this study calculated the viscoelastic mechanical parameters of plant fibers. It also examined the effects of cellulose crystallinity and lumen porosity on fiber structural stiffness and viscoelastic properties, identifying these as key factors in the mechanical behavior of plant fibers. Due to their significant economic potential, the feasibility of using tobacco plant fibers as bio-based materials is being explored.